Can policy participation behavior improve the production efficiency of grassland and animal husbandry: A test based on the threshold effect perceived by herdsmen - Xin Zhang; Xiaolong Yuan; Haiying Liu (PLoS ONE, 2026)
Based on survey data from 536 pastoral households in Inner Mongolia, this study employs the Propensity Score Matching (PSM) method to estimate the Average Treatment Effect on the Treated (ATT) of herders’ participation in grassland ecological compensation policies on their grass and animal husbandry production efficiency during the first and second policy rounds. Furthermore, we utilize herders’ perceptions as a threshold variable to investigate the nonlinear effects of policy participation on production efficiency. The results indicate that: (1) Policy participation significantly suppressed production efficiency during the first policy period, while its effect in the second period was statistically insignificant. (2) Threshold regression models reveal a nonlinear, U-shaped relationship between policy participation and production efficiency, dependent on herders’ overall, economic, and loss perceptions. Specifically, significant double-threshold effects were identified for these three perception types. While overall and loss perceptions remain in the significant inhibitory phase at the lower threshold range, economic perception has already surpassed its lower threshold, enabling policy participation to effectively promote production efficiency. In contrast, only single-threshold effects were found for ecological and emotional perceptions, with policy participation showing no significant positive effect even at higher perception levels.